Design of multi-channel data acquisition frontend board for partial discharge monitoring system - Wang, Wenbo (Nanyang Technological University, 2024)
This dissertation presents the design and implementation of a multi-channel data acquisition (DAQ) frontend board for partial discharge (PD) monitoring systems. PD is a key indicator of insulation degradation in high voltage electrical equipment and requires accurate and robust detection methods. The DAQ board aims to improve the performance of PD detection by employing multiplexing, analog signal processing, and analog-to-digital conversion techniques. The board consists of several components, such as power management, multiplexer, automatic gain control loop, filter, ADC interface, and phase acquisition circuit. The board can capture PD signals from multiple sensors with high speed, high precision, and low noise. The board was tested in laboratory and field environments, and the results showed that it can effectively detect and measure PD pulses with different characteristics and patterns. The board can also be integrated with advanced algorithms for PD diagnosis and classification. The dissertation provides a comprehensive and detailed account of the design, development, and testing process of the DAQ board, as well as the challenges, solutions, and future work.